Measurement equivalence of the Wong and Law Emotional Intelligence Scale across self and other ratings - LIBBRECHT, Nele (Institutional Knowledge at Singapore Management University, 2010)
There exist a variety of measurement instruments for assessing emotional intelligence (EI). One approach is the use of other reports wherein knowledgeable informants indicate how well the scale items describe the assessed person's behavior. In other reports, the same EI scales are typically used as in self-reports. However, it is not known whether the measurement structure underlying EI ratings is equivalent across self and other ratings. In this study, the measurement equivalence of an extant EI measure (Wong and Law Emotional Intelligence Scale [WLEIS]) across self and other ratings was tested. Using multiple group confirmatory factor analysis, the authors conducted a sequence of increasingly more restrictive tests of equivalence across self and other ratings. The WLEIS was found to be configurally and metrically invariant across self and other ratings. However, there was no evidence for structural invariance between rater groups. Future research is needed to test the equivalence of other EI measures across self and other ratings.